Antibacterial effect of silver nanoparticles on talc composites - Shameli, Kamyar; Ahmad @ Ayob, Mansor; Al-Mulla, Emad A. Jaffar; Shabanzadeh, Parvaneh; Bagheri, Samira (Springer, 2015)
Silver nanoparticles (Ag NPs) have been synthesized by using a chemical reducing method in the external space of talc layers as a solid support at room temperature. NaBH4 and AgNO3 were used as a reducing agent and silver precursor, respectively. The interlamellar space limits were without many changes and, therefore, Ag NPs formed on the exterior surface of talc composites with mean diameters 7.60–13.11 nm for different silver nitrate concentrations. The antibacterial effects of different sizes of Ag NPs in talc were investigated against Gram-positive (i.e. Staphylococcus aureus and methicillin-resistant S. aureus) and Gram-negative (i.e. Escherichia coli) bacteria by the disk diffusion method using Mueller–Hinton Agar. The AgNO3 was found to have significant antibacterial activity against Ag NPs that did not indicate any antibacterial effects. These results showed that Ag NPs entrapped in the surface of talc layers cannot be used as effective growth inhibitors in different biological systems.